The effect of "mavizˮ on memory improvement in university students: A randomized open-label clinical trial - Reza Mirheidary; Seyyed Saeed Esmaeili; Mohammad reza Shaeiri; Mohammad Gholami Fesharaki (Mashhad University of Medical Sciences, 2020)
Objective: Numerous studies demonstrated the effect of grape on memory improvement. According to Iranian traditional medicine, "mavizˮ as a specific type of dried grapes can effectively improve memory. However, there is no reported clinical trial on the effect of "mavizˮ on memory improvement in humans. Hence, this study was conducted to investigate "mavizˮ effect on memory in university students. Materials and Methods: This randomized open-label clinical trial was conducted on a total number of 53 students of Shahed University, Tehran, Iran, from November 2017 to February 2018. The participants were randomly allocated into an intervention group (receiving "mavizˮ, 25 g in the morning for 4 weeks) or a control group (who did not take "mavizˮ). The Digit Span Task and the N-Back Task were used for the measurement of working memory at the pre- and post-intervention stages. Results: According to the results, no significant differences were found between the two groups regarding age, gender, marital status, and initial working memory test scores. "mavizˮ consumption produced a highly significant improvement in total working memory score in the Digit Span Task (5.18 vs. 2.35, p<0.001) and Acoustic Memory Span (1.29 vs. 0.62, p=0.021). Moreover, "mavizˮ consumption significantly increased the percentage of true responses in the N-Back Task and reduced the mean reaction time in the first level of the task. Conclusion: "mavizˮ consumption was improved working memory in young healthy adults.